The Influence of Intestinal Tract and Probiotics on the Fate of Orally Administered Drugs - Stojancevic, M.; Bojic, G.; Al-Salami, Hani; Mikov, Momir (Horizon Scientific Press, 2013)
Although the liver has long been considered as a main organ responsible for drug metabolism, the role of the gut metabolizing enzymes and the gut microflora is becoming more profoundly evident in drug metabolism, absorption and overall efficacy. This review will explore various mechanisms by which the gut-microflora influences drug pharmacokinetics including biotransformation, bioactivation, and biodegradation as well as up- or down-regulation of the epithelial transporters. The gut-luminal fluids, intestinal mucosa and gut microflora contain high concentrations of various enzymes which are responsible for the oxidation, hydrolysis and conjugation of drugs. Such metabolic reactions may lead to either drug over- or under-dosing, which impacts the drugs efficacy and safety. The processes, by which the intestinal enzymes and gut-protein transporters influence drug pharmacokinetic parameters, will be detailed. Since the intestinal microflora plays an important role in physiological, nutritional, metabolic, and immunological processes in human body, there is currently some interest in the manipulation of its composition and activity by administering probiotics. This review will also examine the capacity of probiotics to interact with resident microbial community, affecting the respective enzymes or by providing their own specific enzymatic activities that may consequently change the bioavailability and pharmacological activity of concomitantly taken drugs.